Analisis Daya Tarik Iklan Shopee Flash Sale 10:10 Special Super Brand Day - Khairunnisa; Pranawukir, Iswahyu; Arifin, Moh. Syamsul; Launtu, Ansir; Setianti, Yanti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study analyzes the appeal in Shopee's Flash Sale 10:10 Special Super Brand Day advertisement. The advertisement employs a combination of bright visual elements and compelling narratives to attract consumer attention and drive purchase behavior. Through a qualitative approach, the research explores how these elements contribute to the effectiveness of the advertisement, including their impact on consumer psychology, such as the phenomenon of Fear of Missing Out (FOMO). The findings indicate that the use of color, interactive design, and influencer engagement significantly enhance consumer purchase interest. This research provides valuable insights for marketing strategies in the digital era.